2004
DOI: 10.1093/ndt/gfh499
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan reduced advanced glycation end-products accumulation and diminished nitro-oxidative stress in type 2 diabetic KK/Ta mice

Abstract: These findings suggest that candesartan, an ARB, reduces AGE accumulation and subsequent albuminuria by down-regulating the NADPH oxidase p47phox component and iNOS expression and by attenuating RAGE expression in type 2 diabetic KK/Ta mouse kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 15 publications
6
67
0
Order By: Relevance
“…13 However, to our knowledge, this is the first report that ARBs inhibit TNF␣-induced RAGE expression in human endothelial cells, supporting that ARBs have antiatherogenic effects. TNF␣-induced endothelial RAGE expression is regulated by the activation of the NF-B site in the RAGE promoter.…”
Section: Arbs Reduce the Tnf␣-induced Rage Protein And Mrna Expressionmentioning
confidence: 58%
“…13 However, to our knowledge, this is the first report that ARBs inhibit TNF␣-induced RAGE expression in human endothelial cells, supporting that ARBs have antiatherogenic effects. TNF␣-induced endothelial RAGE expression is regulated by the activation of the NF-B site in the RAGE promoter.…”
Section: Arbs Reduce the Tnf␣-induced Rage Protein And Mrna Expressionmentioning
confidence: 58%
“…It has been reported that the ARBs olmesartan [9][10][11] and candesartan 12) inhibited the formation and accumulation of AGEs in vitro 9) and in diabetic animal models. [10][11][12] However, whether they can do so clinically is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Also, an association between AGEs and diabetic microangiopathy has been reported, and intervention to reduce AGEs is considered an important strategy in treating diabetic nephropathy. 8) Miyata, et al reported that ARBs or angiotensin-converting enzyme inhibitors (ACE-Is) decreased AGE formation in vitro via radical scavenging and transition metal chelation, 9) and it has been shown that some ARBs reduced renal AGE accumulation and proteinuria in diabetic rodents in vivo [10][11][12] to a degree similar to that of an ACE-I. 13) Sebekova, et al reported that treatment with the ACE-I ramipril for 2 months significantly decreased the fluorescent AGE level in 12 subjects with nondiabetic nephropathy.…”
mentioning
confidence: 99%
“…The resulting c-DNA was amplified with a Takara PCR Thermal Cycler (Takara Shuzo Co., Ltd., Kyoto, Japan). The sequences of RAGE primers were as follows: GAPDH, sense 5'-AGC CGC ATC TTC TTG TGC A-3', and antisense 5'-GCC GTG AGT GGA GTC ATA CT-3'; and RAGE, sense 5'-CAG GGT CAC AGA AAC CGG-3', and antisense 5'-ATT CAG CTC TGC ACG TTC CT -3' [4]. mRNA of TGF-b was analyzed with mouse transforming growth factor-beta (TGF-b) and that of GAPDH with a Genes Dual-PCR Kit (Maxim Biotech Inc., MD, USA).…”
Section: Semi-quantitative Rt-pcr For Detection Of Receptor For Advanmentioning
confidence: 99%